2005
DOI: 10.1189/jlb.0804453
|View full text |Cite
|
Sign up to set email alerts
|

Binding of pregnancy-specific glycoprotein 17 to CD9 on macrophages induces secretion of IL-10, IL-6, PGE2, and TGF-β1

Abstract: Pregnancy-specific glycoproteins (PSGs) are a family of secreted proteins produced by the placenta, which are believed to have a critical role in pregnancy success. Treatment of monocytes with three members of the human PSGs induces interleukin (IL)-10, IL-6, and transforming growth factor-beta(1) (TGF-beta(1)) secretion. To determine whether human and murine PSGs have similar functions and use the same receptor, we treated wild-type and CD9-deficient macrophages with murine PSG17N and human PSG1 and -11. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 54 publications
5
70
0
2
Order By: Relevance
“…Binding of pregnancy-specific glycoprotein 17 to CD9 on macrophages stimulates secretion of various interleukins, prostaglandin E 2 , and TGF␤. 56 Binding of a monoclonal anti-CD82 antibody to KAI1/CD82 on T lymphocytes, apparently acting as a pseudo-ligand, has been shown to induce downstream effects on activation and cytoskeletal reorganization. 57 Most recently, KAI1 expressed on tumor cells was shown to interact with DARC, a cell-surface protein on vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of pregnancy-specific glycoprotein 17 to CD9 on macrophages stimulates secretion of various interleukins, prostaglandin E 2 , and TGF␤. 56 Binding of a monoclonal anti-CD82 antibody to KAI1/CD82 on T lymphocytes, apparently acting as a pseudo-ligand, has been shown to induce downstream effects on activation and cytoskeletal reorganization. 57 Most recently, KAI1 expressed on tumor cells was shown to interact with DARC, a cell-surface protein on vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD9, a member of the tetraspanin superfamily, is required for cell-cell fusions in which fertilization takes place (Le Naour et al 2000) and also in myogenesis (Tachibana & Hemler 1999). In macrophages, CD9 regulates secretions of IL10 and IL6 via the cAMP/PKA signaling pathway (Ha et al 2005). We hypothesized that CD9 regulates ERVWE1 gene expression through cAMP/PKA signaling pathway and a transcription factor GCM1 in human trophoblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…CD9 is the only receptor reported to bind the Psg family proteins including Psg17 and Psg19 (Waterhouse et al, 2002). Given that the highly conserved amino acid sequence and the domain structure among Psgs17, 18 and 19, we speculated that Psg18 might also bind to CD9 (Ha et al, 2005). We found that CD9 is highly expressed by CD11b + DCs that is a major population of DCs residing in the SED in PP (Fig.…”
Section: Psg18 Protein Is Predominantly Expressed In Faementioning
confidence: 69%
“…In addition, CD11b + DC was found to highly express the Psg receptor, CD9. The binding of Psgs to CD9 has been reported to induce Th2 cytokines IL-10 and IL-6 as well as TGF-β 1 in human monocytes and murine macrophages (Ha et al, 2005). These observations raise the possibility that Psg18 may condition DCs to produce Th2 cytokines via CD9, although further investigation is required to test this hypothesis.…”
Section: Discussionmentioning
confidence: 83%